The growth-employment-poverty nexus in Latin America in the 2000s: Costa Rica country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
In the 2000s, Costa Rica experienced moderate economic growth and a general improvement in labour market conditions. From 2000 to 2012, Costa Rica grew at the Latin American average. Most labour market indicators improved during 2001 - 09 and 2010 - 12 (the series with comparable data). However, the unemployment rate increased in both periods, the mix of employment by occupations polarized from 2010 to 2012, and some poverty and inequality indicators increased from 2010 to 2012. The international crisis had substantial negative effects on the economic growth rate, unemployment, poverty, and inequality indicators, and not all of them recovered after the crisis.
Keywords: O15; J01; J30; 330; Costa Rica; Latin America; inclusive growth; labour market; poverty